(untitled) (The Review of Diabetic Studies, 2025)
Postoperative recovery is a complex and dynamic process influenced by multiple clinical, functional, and psychosocial factors. Collaboration between nurses and physiotherapists is essential for accelerating functional recovery, preventing complications, and improving patient outcomes. This systematic review examines evidence from 2020–2025 regarding how interdisciplinary collaboration contributes to enhanced postoperative recovery across various surgical populations. Six major databases were searched following PRISMA 2020 guidelines. Fourteen studies met the inclusion criteria, including randomized controlled trials, cohort studies, and mixed-methods research. Findings demonstrate that coordinated interdisciplinary care significantly improves pain control, early mobilization, length of stay, pulmonary function, adherence to rehabilitation protocols, and patient satisfaction. Collaborative models such as early mobility teams, enhanced recovery after surgery (ERAS) pathways, and multidisciplinary rehabilitation units were most effective. Limitations include heterogeneity in interventions, insufficient reporting of collaborative mechanisms, and lack of standardized outcome measures. The review concludes that structured collaboration between nurses and physiotherapists is a critical determinant of postoperative recovery and recommends the adoption of integrated protocols, joint rounds, shared documentation, and continuous team-based training.